1996
DOI: 10.1088/0967-3334/17/4a/005
|View full text |Cite
|
Sign up to set email alerts
|

Fast EIT data acquisition system with active electrodes and its application to cardiac imaging

Abstract: A wide-band high-speed data acquisition system for electrical impedance tomography (EIT) is described. 32 active electrodes are used in the system, half of them as receive electrodes and the other half as drive electrodes. A buffer is mounted on the back of each receive electrode and a current source on each drive electrode. A multielectrode system with active electrodes was built to make it convenient to attach all the electrodes on the human thorax. The system is suitable for both dynamic imaging and multifr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Since its introduction, the hardware and software have been improved continuously. 23,24 Hahn and coworkers 25 developed more advanced algorithms for the analysis of dynamic physiologic phenomena with low amplitudes than was initially supplied (Mark I or DAS-01P; Royal Hallamshire Hospital; Sheffield, UK). Thus, they introduced the f-EIT and the averaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, the hardware and software have been improved continuously. 23,24 Hahn and coworkers 25 developed more advanced algorithms for the analysis of dynamic physiologic phenomena with low amplitudes than was initially supplied (Mark I or DAS-01P; Royal Hallamshire Hospital; Sheffield, UK). Thus, they introduced the f-EIT and the averaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo studies have shown that spectral impedance properties are more sensitive and specific than discrete frequencies alone [21]. One approach to improving the spectral range of the probe would be to consider using active electronics located near to the probe tip similar to [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Barber and Brown found a spatial resolution of approximately 8% of the thorax diameter, so that a resolution of 8 mL is achieved [33]. Since its introduction the hardware and software have been improved continuously [34,35]. Hahn and colleagues developed more advanced algorithms for the analysis of dynamic physiological phenomena with low amplitudes.…”
Section: Discussionmentioning
confidence: 99%